Strategy To Improve The Competitiveness Of The Dried Fish Processing Industry In Bandar Lampung City - Irawati, Luluk; Unteawati, Bina; Zaini, Muhammad (ABEC Indonesia, 2024)
This study aims to create a strategy model to improve the competitiveness of the dried fish processing industryin Bandar Lampung city. This study is a survey study with a population of dried fish processors in Teluk Betung BaratDistrict. Primary data and secondary data are used in this study, then the data is analyzed quantitatively and qualitatively,SWOT analysis. The strategy formed is growth seen from the IE matrix value in quadrant 5 with a score value of IFE(2.64) and EFE (2.86), the right alternative strategy through marketing development is digital marketing to supportfishermen's income, in addition there needs to be an alternative cage business as an anticipation of the availability ofuncertain raw materials